Analysis of anatomical variations of intrapelvic vessels for advanced pelvic surgery - Atsushi Hamabe; Takashi Harino; Takayuki Ogino; Tsukasa Tanida; Shingo Noura; Shunji Morita; Keizo Dono (BMC Surgery, 2020)
Abstract Background In pelvic surgery, it is important to anticipate potential anatomic variations, which may be unknown, and inter-relationships among intrapelvic vessels. Here, we comprehensively analyzed intrapelvic vessel patterns. Method This retrospective analysis included 81 patients that underwent colorectal surgery in our institution in 2016. A total of 162 half-pelvises were imaged with contrast-enhanced computed tomography. We scrutinized thin-slice images. Results We found variations in the number of internal iliac veins. In 47.5% of cases, one internal iliac vein drained into the ipsilateral common iliac vein in both halves of the pelvis. In the other cases, several internal iliac veins were observed in one or both halves of the pelvis. We analyzed the inter-relationships between the superior gluteal artery and the sacral nerve plexus in pelvic halves. Superior gluteal arteries ran between the 5th lumbar nerve and 1st sacral nerves, in 82% of halves, and lateral to the 5th lumbar nerve, in 17% of halves. Dorsally, the superior gluteal artery ran on the medial side of the internal iliac vein in 15% of halves. In 28% of half-pelvises, two superior gluteal veins were observed. Superior gluteal veins passed through the sacral nerve plexus lateral to 5th lumbar, between 5th lumbar and 1st sacral, and between 1st and 2nd sacral nerve, in 42.0, 47.5, and 37.7% of halves, respectively. We evaluated the rate of symmetric pelvic anatomies, and found that all anatomic variations formed symmetrically, except the number of internal iliac veins. Conclusion This study clarified the anatomical variations of intrapelvic vessels and their inter-relationships. These findings will benefit our understanding of pelvic anatomy and enhance the safety of radical surgery for treating pelvic diseases.